Special Job Exchange Management (Bkk) In Improving Absorb Work And Growentrepreneurshipstudent At SMKN 1 Pacet Cianjur And SMKN Development Lembang Farm - Gunawan, Edi; Syamsudin, Abin; Iriantara, Yosal; Najmul Hidayat, Ayi (International Journal of Educational Research & Social Sciences, 2022)
The purpose of education in the 1945 Constitution is to educate the nation's life and participate in world peace. Education is an effort to develop existing abilities and potential to become quality human beings. Vocational High Schools were chosen as institutions that are able to produce graduates who can directly enter the workforce. The purpose of this study was to obtain data and examine the Special Job Market Management in increasing job absorption and fostering student entrepreneurship at SMKN 1 Pacet, Cianjur Regency and Vocational School for Agricultural Development Lembang. The research uses a qualitative approach. With the case study method, the focus is on examining a particular case or phenomenon in society which is carried out in depth by studying the background, circumstances, and interactions that occur. The data collection methods in this study were conducted interviews, observations and documentation studies. The results of this study indicate that Special Job Exchange Management is effective in increasing the absorption of student work and fostering entrepreneurship in the field of Agriculture and Agribusiness at SMKN, as proclaimed by the Governor of West Java, the Target is Millennial Farmers, then Agriculture is the third largest sector that contributes to the economic cycle. in West Java, so that implementation planning, organizing, monitoring and evaluation need to be carried out in vocational schools as partners in increasing student work absorption and fostering entrepreneurship in the field of agriculture and agribusiness. , this is a problem while SMK is a place to print the younger generation in innovating and developing talent.